Answers
Answered by
3
Hope this helps you...
Attachments:
![](https://hi-static.z-dn.net/files/da9/cf5a9d93ee029924f585a5c09d1b7517.jpg)
jithakral93:
Thank you
Answered by
2
The Solution is:-
=>4x²+8x+3
Now break the middle term to get 12x² and we found 6x+2x for middle term so that on multiplying we will get 12x² and on add we will get 8x
=> 4x²+6x+2x+3
=> 2x(2x+3)+1(2x+3)
=> (2x+1)(2x+3)
Conclusion:- (2x+1)(2x+3) is the answer.
✡Be Brainly✡
=>4x²+8x+3
Now break the middle term to get 12x² and we found 6x+2x for middle term so that on multiplying we will get 12x² and on add we will get 8x
=> 4x²+6x+2x+3
=> 2x(2x+3)+1(2x+3)
=> (2x+1)(2x+3)
Conclusion:- (2x+1)(2x+3) is the answer.
✡Be Brainly✡
Similar questions
Computer Science,
8 months ago
Hindi,
8 months ago
Science,
8 months ago
Science,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago
Science,
1 year ago
Computer Science,
1 year ago